Socio-cultural factors that influence 50-year-old users for papanicolau taking from a nasca hospital: Factores socioculturales que influyen en las usuarias de 50 años para la toma de papanicolau de un hospital nasca - Parra Zambrano, Ashli Rosa Coraima (2023)
Objective: The objective of this study was to determine the sociocultural factors in 50-year-old users for Pap smears at the Ricardo Cruzado Rivarola de Nasca hospital during the period December 2021 - February 2022. Material and Methods: Observational, analytical, and prospective study. The study population is made up of 80 50-year-old users who attend the Ricardo Cruzado Rivarola hospital for Pap tests at the gynecology-obstetrics office and the sample is 67 users, selected by non-probabilistic sampling for convenience. Results: For the first analysis, in simple and multiple regression, it was found that women with high levels of knowledge had a 384% and 382% higher frequency of having ever undergone a PAP test compared to those with low levels of knowledge. Conclusions: The level of knowledge about the PAP has a relevant influence on having carried out a PAP; but also the women who had a high level were the ones who had the highest frequency of having done it. This added to the number of children; possibly because in the circles of women with children one of the topics to be discussed is about maternal health and within them the PAP.